A case for expanding carrier testing to include actionable X‐linked disorders. Issue 11 (19th September 2018) - Rope, Alan F.; Kauffman, Tia L.; Himes, Pat; Amendola, Laura M.; Punj, Sumit; Akkari, Yassmine; Potter, Amiee; Davis, James V.; Schneider, Jennifer L.; Reiss, Jacob A.; Gilmore, Mari J.; McMullen, Carmit K.; et al.
Key Clinical Message: A research study utilizing whole‐genome sequence analysis for preconception carrier screening provided a genome‐first detection of a severe de novo Factor VIII mutation in a woman with implications for pregnancy management and life‐saving interventions of her newborn son, and a challenge to the existing paradigm regarding carrier testing. Abstract : A research study utilizing whole‐genome sequence analysis for preconception carrier screening provided a genome‐first detection of a severe de novo Factor VIII mutation in a woman with implications for pregnancy management and life‐saving interventions of her newborn son, and a challenge to the existing paradigm regarding carrier testing.